Prioritization of copper for the use in photosynthetic electron transport in developing leaves of hybrid poplar - Shahbaz, Muhammad; Ravet, Karl; Peers, Graham; Pilon, Marinus (Frontiers in Plant Science, 2015)
Plastocyanin (PC) is an essential and abundant copper (Cu) protein required for photosynthesis in higher plants. Severe copper deprivation has the potential to cause a defect in photosynthetic electron transport due to a lack in PC. The Cu-microRNAs, which are up-regulated under Cu deficiency, down-regulate the expression of target Cu proteins other than PC, cytochrome-c oxidase and the ethylene receptors. It has been proposed that this mechanism saves Cu for PC maturation. We aimed to test how hybrid poplar, a species that has capacity to rapidly expand its photosynthetically active tissue, responds to variations in Cu availability over time. Measurement of chlorophyll fluorescence after Cu depletion revealed a drastic effect on photosynthesis in hybrid poplar. The decrease in photosynthetic capacity was correlated with a reduction in PC protein levels. Compared to older leaves, PC decreased more strongly in developing leaves, which also lost more photosynthetic electron transport capacity. The effect of Cu depletion on older and more developed leaves was minor and these leaves maintained much of their photosynthetic capacity. Interestingly, upon resupply of Cu to the medium a very rapid recovery of Cu levels was seen in the younger leaves with a concomitant rise in the expression and activity of PC. In contrast, the expression of those Cu proteins, which are targets of microRNAs was under the same circumstances delayed. At the same time, Cu resupply had only minor effects on the older leaves. The data suggest a model where rapid recovery of photosynthetic capacity in younger leaves is made possible by a preferred allocation of Cu to PC in younger leaves, which is supported by Cu-microRNA expression.